When compelled to FB around academic texts: Postgraduate students reflected on their online experience - Shaik Abdullah, Sarimah; Yaacob, Aizan; Abdul Rahim, Fauziah (Universiti Utara Malaysia Press, 2013)
Purpose – This paper is part of a larger study which explored postgraduate students talk around academic texts via Facebook (FB). Our exploration is largely guided by the idea of reading as a social practice. In this paper, we specifically focus on the students’ reflections of their online experience of talking around academic texts. Method – The qualitative data used in this paper were derived from students’ reflective diaries, students’ FB interactions, and informal conversations and were collected from a group of students (27) attending a master’s class in distance learning mode.Thematic analysis was conducted to examine the themes that emerged to represent their reflections.Findings – The students’ reflections were grouped into two major categories: convenience and facilitation of learning.Students’ reflection on the convenience afforded by the FB talk centered mainly on the idea of distance and time. Their reflections on the facilitation of learning were broken down into the following themes: safe environment to explore, social support, self-regulation and autonomy.A separate category, “FB entries need responding”, was assigned to students’ comments about the importance of lecturer’s and group members’ feedback.Value – This study revealed the potential of FB as a convenient, safe and an informal avenue for students to share their understandings and reading-related problems.The informal nature of their FB experience supported free exploration of ideas without the worry of having to appear “clever”.